FORMS OF VIOLENCE AGAINST CHILDREN IN PUBLIC PRE-PRIMARY SCHOOLS IN NAIROBI CITY COUNTY - W. Catherine, Gichuba,; B. Teresa, Dr. Mwoma,; W. Juliet, Dr. Mugo, (IJRDO - Journal of Social Science and Humanities Research, 2017)
Violence against children is a common phenomenon worldwide, which may be presented in different forms that includes physical, psychological and sexual. The Kenyan government has enacted different Acts of law to provide support and direction in the process of protecting all children. However, despite the existence of the acts and efforts put in place, violence against children is still rampant and studies done have mostly focused on women and girls, yet both genders are at risk. This article, therefore presents findings of a study conducted in Nairobi City County focusing on the forms of violence against children in pre-primary schools. This study was anchored on the culture of violence theory which emphasizes on violence as a product of sub-cultures, systems and structures in the society. Descriptive survey design was adopted for the study. Sampling technique used was multi-stage whereby purposeful and simple random sampling procedures were used and a study sample size of 168 identified that comprised of preschool teachers, parents and children officers. Data was collected using a questionnaire. The findings showed that violence against children was in existence and occurred in different forms which included physical, psychological and sexual. Recommendations were made for different stakeholders to ensure provision and maintenance of a child friendly environment both in school and at home and also work towards ending physical and humiliating punishments to all children and the government to ensure effective monitoring and evaluation on implementation of the existing policies Further research needs to be carried out to establish the causes of violence against children in Nairobi City County and a replication of the current study in other counties to find out if similar trends exist.